Methyl jasmonate induces selaginellin accumulation in Selaginella convoluta - Reginaldo, Fernanda Priscila Santos; Bueno, Paula Carolina Pires; Lourenço, Estela Mariana Guimarães; de Matos Costa, Isabelly Cristina; Moreira, Letícia Gondim Lambert; de Araújo Roque, Alan; Barbosa, Euzébio Guimarães; Fett-Neto, Arthur Germano; Cavalheiro, Alberto José [UNESP]; Giordani, Raquel Brandt (Springer Nature, 2023)
Introduction: Selaginellins are specialized metabolites and chemotaxonomic markers for Selaginella species. Despite the growing interest in these compounds as a result of their bioactivities, they are accumulated at low levels in the plant. Hence, their isolation and chemical characterization are often difficult, time consuming, and limiting for biological tests. Elicitation with the phytohormone methyl jasmonate (MeJA) could be a strategy to increase the content of selaginellins addressing their low availability problem, that also impairs pharmacological investigations. Matherials and methods: In this study, we examined MeJA elicitation in Selaginella convoluta plants, a medicinal plant found in northeastern Brazil, by treating them with two different concentrations (MeJA: 50 and 100 µM), followed by chemical profiling after 12, 24 and 48 h after application. Samples were harvested and analyzed by liquid chromatography coupled to tandem mass spectrometry (LC-MS/MS). Results and discusscion: MeJA treatment significantly impacted the chemical phenotype. Regarding shoots differences in the time-dependent increased accumulation of all metabolites when plants were subjected to 100 µM MeJA were observed while in roots, most metabolites had their concentrations decreased in a time-dependent fashion at the same conditions. Results support organ, MeJA concentration and time post-treatment dependence of specialized metabolite accumulation, mainly the flavonoids and selaginellins. The amount of Selaginellin G in shoots of MeJA-treated specimens increased in 5.63-fold relative to control. The molecular networking approach allowed for the putative annotation of 64 metabolites, among them, the MeJA treatment followed by targeted metabolome analysis also allowed to annotate seven unprecedented selaginellins. Additionally, the in silico bioactive potential of the annotated selaginellins highlighted targets related to neurodegenerative disorders, antiproliferative, and antiparasitic issues. Taken together, data point out MeJA exposure as a strategy to induce potentially bioactive selaginellins accumulation in S. convoluta, this approach could enable a deep investigation about the metabolic function of these metabolites in the genus as well as regarding pharmacological exploration of the undervalued potential.
Keywords: Lycophytes; MeJA; Phenolic derivatives; Selaginella convoluta; Selaginellaceae; Selaginellins